2014
DOI: 10.1053/j.gastro.2014.02.055
|View full text |Cite
|
Sign up to set email alerts
|

A Listeria Vaccine and Depletion of T-Regulatory Cells Activate Immunity Against Early Stage Pancreatic Intraepithelial Neoplasms and Prolong Survival of Mice

Abstract: BACKGROUND & AIMS Premalignant lesions and early stage tumors contain immunosuppressive microenvironments that create barriers for cancer vaccines. KrasG12D/+;Trp53R172H/+;Pdx-1-Cre (KPC) mice, which express an activated form of Kras in pancreatic tissues, develop pancreatic intraepithelial neoplasms (PanIN) that progress to pancreatic ductal adeno-carcinoma (PDA). We used these mice to study immune suppression in PDA. METHODS We immunized KPC and KrasG12D/+;Pdx-1-Cre mice with attenuated intracellular Liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 46 publications
5
99
0
1
Order By: Relevance
“…Although one prior study linked the Class IA PI3Ks to BTK activation in B cells, recent studies have reported that these proteins regulate similar but distinct signaling pathways in B cells (33, 34). Our studies instead reveal the selective role of the Class IB PI3K isoform PI3Kγ in regulating BTK to control the macrophage response to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Although one prior study linked the Class IA PI3Ks to BTK activation in B cells, recent studies have reported that these proteins regulate similar but distinct signaling pathways in B cells (33, 34). Our studies instead reveal the selective role of the Class IB PI3K isoform PI3Kγ in regulating BTK to control the macrophage response to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Because PDAC development is associated with the emergence of immunosuppressive cell populations including Tregs and myeloid cells 14-16 , we hypothesized that systemic immunosuppression present within tumor-bearing KPC mice may inhibit the ability of Gem+FGK to induce T cell dependent anti-tumor immunity. To examine this hypothesis, we implanted KPC-derived tumor cell lines into syngeneic KPC mice with spontaneous pancreatic tumors (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…For example, FAP + stromal cells in PDA regulate T cell infiltration to PDA via CXCL12/CXCR4 (Feig et al, 2013), but FAP + stromal cells in the KPC model are CD40-negative, and FAP + cell depletion (or CXCR4 inhibition) does not negatively impact T Regs in the way αCD40/chemotherapy does in the same KPC model. Vaccination with recombinant antigen-expressing Listeria is another powerful method to generate anti-PDA T cells (Keenan et al, 2014) but appears to rely on STING activation (Jin et al, 2013; Woodward et al, 2010), unlike αCD40. Other treatments that can mediate T cell responses against PDA include GVAX vaccination (Le et al, 2015; Soares et al, 2015), adoptive transfer of antigen-receptor engineered T cells (Stromnes et al, 2015), and CSF-1R inhibition (Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%